The Roles of Local Government in Preventing Woman Trafficking in Laws No 21 of 2007 Perspective That Concer to Crime of Human Trafficking in District of Bone - Paikah, Nur (International Journal of Scientific Research and Management (IJSRM), 2018)
This research aims to analyze the process the role of government of human trafficking. Research was conducted at Bone Regency. Methods used the case study method by using a qualitative approach. The results showed human trafficking is one of the crimes against humanity, because this act has violated human rights, and the majority are victims of women and children. Referring to the Law that, every human being, especially women and children, has the right to live peacefully and properly as they should. Therefore, the right of life of every human being cannot be reduced by anyone and under any circumstances including not allowed to be traded, especially women and children. This is where the role of the government, especially the local government of Bone Regency, seeks to guarantee the protection of positive rights for them for their lives. In this case the local government of Bone Regency provides protection and prevention of human trafficking, especially women and children as a form of respect, recognition and protection of human rights is stated explicitly in Article 58 of Law Number 21 of 2007 concerning Crime of Trafficking in Persons.